Students’ Viewpoint of Automatic Translation Tools in EFL Classroom - Yudianto, Heri; Surtikanti, Monika; Agung, Antonius (Jurnal Pedagogy, 2025)
The mismatch between institutional expectations and students' learning needs has become a concern in the digital era, particularly in EFL classrooms. Universities emphasize academic values like originality and critical thinking, while students seek efficient learning methods. A significant technological advancement is the implementation of Automatic Translation Tools (ATTs), which have achieved greater accuracy due to advancements in artificial intelligence. This qualitative case study explores students' viewpoints on using ATTs in a Catholic university in West Kalimantan, which emphasizes originality in academic work. Data were collected from 41 respondents in the 6th semester of the English education program using questionnaires and interviews. Results show that respondents favor ATTs as they help translate complex texts, increase vocabulary, and support task completion. However, reliance on ATTs in communication raises concerns as it can inhibit independent language and critical thinking. This tool is employed for academic and non-academic applications, including social media. They emphasized balancing translation tools with academic integrity and the need for guidelines for responsible use, aligning with the University's values.